Toll‐like receptor 6 mediated inflammatory and functional responses of zinc oxide nanoparticles primed macrophages. Issue 3 (July 2014) - Roy, Ruchi; Singh, Sunil K.; Das, Mukul; Tripathi, Anurag; Dwivedi, Premendra D.
Summary Macrophages are among the most sensitive immune cells because of their phagocytic activity and are prone to become dysfunctional or not able to perform properly if nanoparticle load increases. We have previously reported that zinc oxide nanoparticles (ZNPs) induce inflammatory responses in macrophages that contribute to their death. Recognition of ZNPs by pattern recognition receptors such as toll‐like receptors (TLRs) might be a factor in the initiation of these responses in macrophages. Therefore, in this study we explored the role played by TLR6 and mitogen‐activated protein kinase (MAPKs) pathways in the inflammatory responses of macrophages during ZNPs exposure. ZNPs‐activated macrophages showed enhanced expression of activation and maturation markers (CD1d, MHC‐II, CD86 and CD71). Among various TLRs screened, TLR6 emerged as the most potent activator for ZNPs‐induced inflammatory responses. Downstream signalling proteins myeloid differentiation 88, interleukin‐1 receptor associated kinase and tumour necrosis factor receptor‐associated factor were also enhanced. On inhibiting MAPKs pathways individually, the inflammatory responses such as interleukin‐1β, interleukin‐6, tumour necrosis factor‐α, cyclooxygenase‐2 and inducible nitric oxide synthase were suppressed. TLR6 silencing significantly inhibited the pro‐inflammatory cytokine levels, reactive nitrogen species generation and inducible nitric oxide synthase expression. Also, inhibition of MAPKs in the absence of TLR6 signalling validated the link between TLR6 and MAPKs in ZNPs‐induced inflammatory responses. TLR6 was found to be co‐localized with autophagosomes. Macrophages lacking TLR6 inhibited the autophagosome marker protein‐microtubule‐associated protein1 light chain 3‐isoform II formation and phagocytosis. These results demonstrate that inflammatory responses caused by ZNPs‐activated macrophages strongly depend on TLR6‐mediated MAPK signalling.